2015
DOI: 10.1155/2015/958192
|View full text |Cite
|
Sign up to set email alerts
|

Use of Selected Essential Oils to Control Aflatoxin Contaminated Stored Cashew and Detection of Aflatoxin Biosynthesis Gene

Abstract: Aspergillus spp. associated with cashew from the regions of Riyadh, Dammam, and Abha were isolated and three different culture media were used to qualitatively measure aflatoxin production by Aspergillus via UV light (365 nm), which was expressed as positive or negative. The obtained data showed that six isolates of A. flavus and four isolates of A. parasiticus were positive for aflatoxin production, while all isolates of A. niger were negative. Five commercially essential oils (thyme, garlic, cinnamon, mint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
(17 reference statements)
8
13
0
Order By: Relevance
“…Zohri et al reported that black pepper, cinnamon, spearmint, cumin, thyme and anise completely inhibited mycotoxin production at a concentration of 1%. Abd El‐Aziz et al found that the 5 tested essential oils (thyme, garlic, cinnamon, mint and rosemary) showed inhibitory effect on the growth and secretion of aflatoxins by A. flavus and A. parasiticus using (HPLC) and the percentage of inhibition increased with increasing the concentration. Razzaghi‐Abyaneh et al reported that the oil extract from Carum carvi L. inhibited only aflatoxin production, with no effect on Aspergillus parasiticus growth.…”
Section: Resultsmentioning
confidence: 99%
“…Zohri et al reported that black pepper, cinnamon, spearmint, cumin, thyme and anise completely inhibited mycotoxin production at a concentration of 1%. Abd El‐Aziz et al found that the 5 tested essential oils (thyme, garlic, cinnamon, mint and rosemary) showed inhibitory effect on the growth and secretion of aflatoxins by A. flavus and A. parasiticus using (HPLC) and the percentage of inhibition increased with increasing the concentration. Razzaghi‐Abyaneh et al reported that the oil extract from Carum carvi L. inhibited only aflatoxin production, with no effect on Aspergillus parasiticus growth.…”
Section: Resultsmentioning
confidence: 99%
“…There is an upstanding relationship between the inhibitory effect of the essential oils and their doses (AbdEl- Aziz et al, 2015, Al-Gahtani et al, 2013Rasooli et al, 2008). The results indicate that the test toxigenic fungus is sensitive to the savory essential oil and particularly sensitive to doses upper than 500 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase consists of methanol:acetic acid:water (20:20:60 v/v/v). The total run time for the separation was approximately 25 min at a flow rate of 1 ml/min (Christian, 1990;Abd-El-Aziz et al, 2015).…”
Section: Determination Of Hplcmentioning
confidence: 99%
“…In view of their different biological properties, EOs have been tested as alternative strategy for combating mycotoxins, especially aflatoxins [29][30][31][32][33][34] (Table 1). EOs are molecules of natural origin, biodegradable, and are therefore considered as a possible alternative to synthetic pesticides [35].…”
Section: Use Of Essential Oils As Antifungal and Antiaflatoxigenic Agmentioning
confidence: 99%